Evaluation of the antimicrobial activity of poultry feed additives with zinc oxide nanoparticles (Research, Society and Development, 2021)
The presence of pathogenic bacteria such as Salmonella spp and Staphylococcus aureus in poultry houses results in huge economic losses, influencing the performance and quality of broiler chicken. These bacteria cause food poisoning due to the consumption of foods containing thermostable enterotoxins produced by them. Studies show that antibiotics used in poultry can cause allergic reactions to humans in addition to increasing bacterial resistance to treatment. Zinc oxide nanoparticles, NPs-ZnO, have been studied because of their excellent antimicrobial potential and because zinc oxide is recognized as a safe substance for consumption at low concentrations. In addition zinc is a micronutrient metabolized by the poultry organism and humans, not being a toxic substance. So the objective of this study was to add antimicrobial properties to poultry feed by the addition of NPs-ZnO and to evaluate antibacterial activity against Gram-negative Salmonella Typhimurium and Gram-positive Staphylococcus aureus bacteria. Different ratios of NPs-ZnO in the diet (1, 2, 3, 4 and 5%, mg g-1) were evaluated by solid diffusion, minimum inhibitory concentration and growth curve. It was found that the concentration of 3% (mg g-1) of NPs-ZnO was the lowest necessary to prevent the growth of studied bacteria being able to be applied in poultry feed to protect them from potential pathogenic bacteria present in the farms.